Blockers on the pseudo-arc - Illanes, Alejandro (Topology Proceedings, 2021)
Let X be a continuum. Given disjoint nonempty closed subsets A and B of X, B does not block A provided that the union of subcontinua of X intersecting A but not intersecting B is dense in X. Answering a question by J. Bobok, P. Pyrih and B. Vejnar in this paper we prove that if P is the pseudo-arc, then there exists a nonempty closed subset D of P such that D blocks each finite set E contained in P D but there exists a nonempty closed subset G P D such that D does not block G.